1998
DOI: 10.4315/0362-028x-61.8.969
|View full text |Cite
|
Sign up to set email alerts
|

Heat Resistance of Salmonella weltevreden in Low-Moisture Environments

Abstract: The heat resistance of Salmonella weltevreden inoculated into flour and heated in hot air was determined for (a) an initial water activity (aw) range of 0.20 to 0.60 prior to heating, (b) a range of storage relative humidities of 6.0 to 35.5% prior to heating, and (c) temperatures of 57 to 77 degrees C. The death curves obtained were biphasic, demonstrating an initial rapid decline in the numbers of survivors (1.0- to 1.5-log reductions) during the first 5 to 10 min of heating for all the temperature-water act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
53
5
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(65 citation statements)
references
References 0 publications
6
53
5
1
Order By: Relevance
“…Because we found that the populations of STEC and salmonellae inoculated with a cocoa drink without sucrose were 51 to 370 times higher than those inoculated with SPS, it was suggested that a vegetable fat such as cacao butter, which is an ingredient of cocoa as well as chocolates, was also a contributing factor for the enhancement of survival of these strains in dry foods. Another noteworthy finding in this study was that the desiccated STEC and Salmonella strains survived the high-temperature exposure to 70°C for 5 h. We are the first to report that desiccated STEC acquires almost the same degree of heat resistance as Salmonella, whose resistance has been reported to increase with decreasing a w levels (2,3,6). These observations clearly indicate that heat sterilization procedures against STEC as well as Salmonella in dry foods should be distinctively different from those in nondried foods, which can be accomplished easily after exposure to 70°C for far less than 5 h. Although the mechanism(s) of the resistance of STEC and salmonellae to dryness demonstrated in this study, or that of gram-negative bacteria in general, remains to be elucidated, the "water replacement hypothesis" (7,20) could be a possible explanation for an underlying mechanism.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Because we found that the populations of STEC and salmonellae inoculated with a cocoa drink without sucrose were 51 to 370 times higher than those inoculated with SPS, it was suggested that a vegetable fat such as cacao butter, which is an ingredient of cocoa as well as chocolates, was also a contributing factor for the enhancement of survival of these strains in dry foods. Another noteworthy finding in this study was that the desiccated STEC and Salmonella strains survived the high-temperature exposure to 70°C for 5 h. We are the first to report that desiccated STEC acquires almost the same degree of heat resistance as Salmonella, whose resistance has been reported to increase with decreasing a w levels (2,3,6). These observations clearly indicate that heat sterilization procedures against STEC as well as Salmonella in dry foods should be distinctively different from those in nondried foods, which can be accomplished easily after exposure to 70°C for far less than 5 h. Although the mechanism(s) of the resistance of STEC and salmonellae to dryness demonstrated in this study, or that of gram-negative bacteria in general, remains to be elucidated, the "water replacement hypothesis" (7,20) could be a possible explanation for an underlying mechanism.…”
Section: Discussionsupporting
confidence: 50%
“…Very low water content in the cells can inhibit or diminish the protein denaturation induced by high-temperature heating through vibration of water molecules to break S-S and hydrogen bonds of intracellular proteins (9). Because of the very low water contents in the desiccated STEC strains and salmonellae, the extent and strength of the vibration of water molecules in these bacteria are considered to be limited substantially, thus preventing the bacteria from denaturation of the membrane proteins and preserving their integrity even during exposure to a very high temperature (2).…”
Section: Discussionmentioning
confidence: 99%
“…This makes the assumption that all bacterial cells within a population have the same heat sensitivity, but significant deviations from linearity have been reported elsewhere (5,9,26,33,40,60). In such cases, curve fitting will give more accurate descriptions of the data than will D values because shoulders or tailing can be incorporated.…”
mentioning
confidence: 97%
“…Considering the fact that the vast majority of these products undergo thermal processing before packaging, it has been suggested that there is a correlation between the low water content of the product and the increased thermal resistance of the pathogen (9,21,24,39,43). Using laboratory models, it was demonstrated that reducing water activity either by desiccation (24,31) or by addition of solutes (2,12,30,37,38) resulted in increased thermal tolerance.…”
mentioning
confidence: 99%